Basaloid Squamous Cell Carcinoma of the Palate: Case Report - Boza Oreamuno DDS, MSc, Yadira V. (Odovtos - International Journal of Dental Sciences, 2017)
Basaloid Squamous Cell Carcinoma (BSCC) is a rare and aggressive variant of squamous cell carcinoma (SCC), with a predilection for the upper aerodigestive tract, the palate being a very rare site of development. It is constituted by a basaloid and a squamous components in variable proportions, however, the histopathological characteristics of the BSCC overlap with other neoplasias. Diagnosis with various immunohistochemical markers such as p63, Ki67, p16, and AE1 / AE3 cytokeratins have become a necessity for the specialist. The objective of this study is to present a case of BSCC in soft palate and to show the importance of the support in the immunohistochemistry for an early histopathological diagnosis. A review of the literature on this pathology is also presented.